2021
DOI: 10.1186/s12933-021-01360-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability in body weight and the risk of cardiovascular complications in type 2 diabetes: results from the Swedish National Diabetes Register

Abstract: Background There is a high incidence of cardiovascular disease in diabetes. Weight variability has been reported as independent risk factor for cardiovascular disease in the general population and preliminarily also in people with type 2 diabetes. Methods Using data from the Swedish National Diabetes Register the possible link between visit-to-visit body weight variability and the risk of cardiovascular complications among people with type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…We pooled the outcomes of studies using cutoffs of 5–10% and > 10% for weight loss. Seven studies [ 24 26 , 32 , 33 , 36 , 37 ] reported the association of weight variability with mortality and CV events. Among them, weight variability was assessed using average successive variability (ASV), coefficient of variation, and standard deviation (SD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We pooled the outcomes of studies using cutoffs of 5–10% and > 10% for weight loss. Seven studies [ 24 26 , 32 , 33 , 36 , 37 ] reported the association of weight variability with mortality and CV events. Among them, weight variability was assessed using average successive variability (ASV), coefficient of variation, and standard deviation (SD).…”
Section: Resultsmentioning
confidence: 99%
“…In 6 studies [ 24 26 , 32 , 33 , 36 ] with a combined study population of 772,563, fluctuation in body weight was associated with increased all-cause mortality and major CV outcomes among T2DM patients. Another study [ 37 ] reported that high weight variability was associated with incident AF (HR [95% CI] 1.16 [1.12–1.20]).…”
Section: Resultsmentioning
confidence: 99%
“…High BWV predicted the development of cardiovascular complications such as non‐fatal myocardial infarction, non‐fatal stroke and all‐cause mortality in T2D. 59 These studies further suggest that any weight loss strategy in people with T2D should be aimed at maintaining the reduction in the long term and avoiding body weight oscillations.…”
Section: Challenges In Achieving Weight and Glycaemic Targets For Ind...mentioning
confidence: 86%
“… 56 , 57 In a real‐world study with Asian patients with T2D, BWV was associated with higher risks of myocardial infarction, stroke and all‐cause mortality. 58 A recent study 59 using data from the Swedish National Diabetes Register of 100,576 people with T2D and without prevalent cardiovascular diseases at baseline evaluated the link between visit‐to‐visit BWV and the risk of cardiovascular complications in a Caucasian population. High BWV predicted the development of cardiovascular complications such as non‐fatal myocardial infarction, non‐fatal stroke and all‐cause mortality in T2D.…”
Section: Challenges In Achieving Weight and Glycaemic Targets For Ind...mentioning
confidence: 99%
“…Excessive weight gain was associated with measures of subclinical atherosclerosis and predictors of cardiovascular events and with higher rates of cardiovascular events in the DCCT/EDIC studies [ 13 , 14 ]. Fluctuation of body-weight, also known as weight cycling, i.e., repeatedly losing and regaining weight [ 15 ], was shown to be an independent predictor of cardiovascular events and mortality risk in the general population [ 16 , 17 ], as well as in people with coronary artery disease [ 18 ], or type 2 diabetes [ 19 , 20 ]. Weight cycling is a potential non-traditional cardiovascular risk factor in patients with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%